Pembacaan Surah Al-Fil dalam Tradisi Mubeng (Studi Living Qur’an di Desa Kepet Kecamatan Dagangan Kabupaten Madiun) - Ahmad Abdul Aziz Aziz; Moh. Alwy Amru Ghozali (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2024)
The mubeng tradition is a long-standing tradition in Kepet Village, Dagangan District, Madiun Regency. In its implementation there is a reading of Surah al-Fil which is one of the surahs in the Koran. This research discusses the living Qur'an that is developing in the Kepet village community. This research uses a qualitative approach in the form of field research. Research results: that this tradition is carried out every Friday night as long as it is not raining and outside the month of Ramadan. The motive for implementing the tradition is divided into two parts. The 'because' motive was because village security was very precarious and worrying at that time, because they hoped for blessings from Allah and because the people were still ordinary people. The motive for 'so' is to obtain security, so that the villagers are comfortable and so that they receive blessings from Allah. There are three meanings of implementing the mubeng tradition, objective meaning, expressive meaning and documentary meaning. The objective meaning is to strengthen ties of friendship, to increase feelings of love for Rasulullah SAW and to appreciate and maintain traditions that have existed for a long time. The expressive meaning is as a means of protecting the village, as a means of seeking blessings, as a means of achieving a wish, as a means of maintaining the comfort of the village from various traditions in accordance with Islamic religious law, as a means of village security from various crimes, as a means of sadaqoh between fellow humans, as a means of maintain the village economy. The meaning of the documentary is that indirectly the practitioners of the tradition memorize Surah al-Fil.